2015
DOI: 10.5897/jmpr2014.5660
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of different African seeds and vegetables and correlation with the contents of ascorbic acid, phenolics and flavonoids

Abstract: The antioxidant capacity of 2 African seeds and 8 vegetables were analyzed using ferric reducing antioxidant power assay (FRAP assay) after water and acetone extractions. The contents of ascorbic acid, phenolics and flavonoids were determined and their correlations with FRAP value were investigated. The results showed that Vernonia amygdalina was stronger (4.84 mM/100 g dry weight (DW)) than other vegetables analyzed in antioxidant capacity based on total FRAP values. Baphia nitida was the lowest in total FRAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…Hence it can be suggested that an antioxidant activity is highly correlated with the TPC than the scavenging power of GA. These results supported the results of other studies [33][34][35][36] . The high correlation between FRAP and CUPRAC, TPC and ORAC can establish a fact that, these assays rely on the common reaction mechanism and that there was no significant correlation between DPPH and the values with FRAP, TPC, and CUPRAC.…”
Section: Correlationssupporting
confidence: 93%
“…Hence it can be suggested that an antioxidant activity is highly correlated with the TPC than the scavenging power of GA. These results supported the results of other studies [33][34][35][36] . The high correlation between FRAP and CUPRAC, TPC and ORAC can establish a fact that, these assays rely on the common reaction mechanism and that there was no significant correlation between DPPH and the values with FRAP, TPC, and CUPRAC.…”
Section: Correlationssupporting
confidence: 93%
“…Moreover, GA is well known to improve the antioxidant status of the human body and induce hepatoprotection by modulating the expression of several oxidative stress genes (Ahmed et al 2015). A previous study also suggested that GA is rich in phenolics which are correlated to its antioxidant than its scavenging power (Edet et al 2015;Mirghani et al 2018;Sahu and Saxena 2013). GA was also reported to decrease superoxide production and MDA and increased TAC and GSH levels in rats (Ali et al 2020).…”
Section: Discussionmentioning
confidence: 97%
“…GA was also reported to decrease superoxide production and MDA and increased TAC and GSH levels in rats (Ali et al 2020 ). Furthermore, the antioxidant capacity of GA may be attributed to its content of different amino acids (Ali et al 2020 ; Khalid et al 2017 ); besides, it has anti-inflammatory and immune-modulatory actions in mice (Edet et al 2015 ; Kamal et al 2018 ) via attenuating C-reactive protein and TNFα and increasing the anti-inflammatory cytokine IL10 (Ali et al 2013 ; Ushida et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GA is well known to improve the antioxidant status of the human body and induced hepatoprotection by modulating the expression of several oxidative stress genes (Ahmed et al, 2015). A previous study also suggested that GA is rich in phenolics which are correlated to its antioxidant than its scavenging power (Edet et al, 2015;Mirghani et al, 2018;Sahu and Saxena, 2013). GA was also reported to decrease superoxide production and MDA and increased TAC and GSH levels in rats (Ali et al, 2010;Al-Yahya et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…GA was also reported to decrease superoxide production and MDA and increased TAC and GSH levels in rats (Ali et al, 2010;Al-Yahya et al, 2009). Furthermore, the antioxidant capacity of GA may be attributed to its content of different amino acids (Ali et al, 2020;Khalid et al, 2017) beside it has anti-in ammatory and immune-modulatory actions in mice (Edet et al, 2015;et al, Kamal 2018) via attenuating C-reactive protein and TNFα and increasing the anti-in ammatory cytokine IL10 (Ali et al, 2013;Ushida et al, 2011).…”
Section: Discussionmentioning
confidence: 99%